Observation of intrinsic fluorescence in cobalt ferrite magnetic nanoparticles by Mn2+ substitution and tuning the spin dynamics by cation distribution. Issue 35 (19th August 2022) - Kumar, Prashant; Pathak, Saurabh; Singh, Arjun; Jain, Komal; Khanduri, H.; Wang, Lan; Kim, Sang-Koog; Pant, R. P.
Abstract : In this work, we report the synthesis and detailed characterization of single-domain, optically active, manganese-substituted cobalt ferrite (CoFe2 O4 ) magnetic nanoparticles without any surface functionalization as prospective fluorescent probes for bio-imaging. Abstract : In this work, we report the synthesis and detailed characterization of single-domain, optically active, manganese-substituted cobalt ferrite (CoFe2 O4 ) magnetic nanoparticles without any surface functionalization as prospective fluorescent probes for bio-imaging. Generally, nanoferrites (NFs) do not show any intrinsic fluorescence and require surface modification to make them fluorescent by functionalization with fluorescent probes. Herein, we observed multi-band fluorescent emission in Co1− x Mn x Fe2 O4 (0.8 ≤ x ≤ 0) NFs synthesized via a one-pot hydrothermal method. The substitution of cobalt by manganese in CoFe2 O4, which has an inner shell electronic transition between its d 5 energy levels, and increase in the concentration of defect centers mainly contributed to the fluorescent characteristics of the as-synthesized NF samples. The two emission bands observed for the Co–Mn NFs are violet and blue bands. The violet band was observed due to the transfer of electrons from the shallow donor level to the valence band ( i.e., near band edge (NBE) emission), while the emission in the blue region can be attributed to the band edge free and bound excitons. Also, the time-resolved photoluminescence studies indicated two decay times, which can be attributed to the blue and violet emission bands. Detailed structural modeling was performed using Rietveld refinement of the X-ray diffraction data and the cation distribution obtained from the modeling was corroborated by the optical properties and spin dynamics of the NFs. The cation distribution of the NF samples indicates that the blue band originates from the 3F → 3p transition in the octahedral sites between the Co 2+ /Mn 2+ ions. Further, a strong ferromagnetic characteristic was observed for the NF samples and the optimized substitution of Mn 2+ ions resulted in an improvement in the saturation magnetization from 68.51 to 80.30 emu g −1, which was corroborated by the Yafet–Kittel model. Further, imparting optical properties in magnetic materials opens a new horizon for the biomedical applications of these materials by capitalizing on their intrinsic fluorescence, which will not hamper their magnetic properties as in the case with external fluorescent probes.